Drug Eluting Stent : Initial observation in Nepalese patients - Rawat, B; Bhatta, Y; Pande, R; Pandey, M; Poudyal, P; Verma, P; Agrawal, P; Chandra, P; Kasliwal, RR (Nepalese Heart Journal, 2004)
Recent studies have shown a marked beneficial effect of drug eluting stents in the prevention of restenosis. The total number of patients who underwent PTCA in our institute were 63, out of which 13 drug eluting stents were used in 11 patients. Among these patients, 9 (81.81%) were male and 2 (27.27%) were female patients within the age range of 41 to 70 years.